A review of the pharmacological action and mechanism of natural plant polysaccharides in depression - Yang, Yu-He; Li, Chen-Xue; Zhang, Ruo-Bing; Shen, Ying; Xu, Xue-Jiao; Yu, Qin-Ming (Frontiers in Pharmacology, 2024)
Depression is a prevalent mental disorder. However, clinical treatment options primarily based on chemical drugs have demonstrated varying degrees of adverse reactions and drug resistance, including somnolence, nausea, and cognitive impairment. Therefore, the development of novel antidepressant medications that effectively reduce suffering and side effects has become a prominent area of research. Polysaccharides are bioactive compounds extracted from natural plants that possess diverse pharmacological activities and medicinal values. It has been discovered that polysaccharides can effectively mitigate depression symptoms. This paper provides an overview of the pharmacological action and mechanisms, intervention approaches, and experimental models regarding the antidepressant effects of polysaccharides derived from various natural sources. Additionally, we summarize the roles and potential mechanisms through which these polysaccharides prevent depression by regulating neurotransmitters, HPA axis, neurotrophic factors, neuroinflammation, oxidative stress, tryptophan metabolism, and gut microbiota. Natural plant polysaccharides hold promise as adjunctive antidepressants for prevention, reduction, and treatment of depression by exerting their therapeutic effects through multiple pathways and targets. Therefore, this review aims to provide scientific evidence for developing polysaccharide resources as effective antidepressant drugs.